MANAJEMEN PARTISIPASI KADER DALAM MENDUKUNG PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) DI PUSKESMAS WAY HALIM KOTA BANDAR LAMPUNG - Zainal Muslim; Sri Indra Trigunarso; Inayah Inayah (JMMS - JURNAL MANAJEMEN MANDIRI SABURAI, 2023)
The most important thing needed is human resources in the form of participation from the community as partners, such as Posyandu cadres, Posbindu cadres, Poskestren cadres, PKK cadres. Management of local community organizations, such as PKK administrators, youth youth groups, recitation managers, and others (Ministry of Health, 2016). According to Ismawati (2010), cadres are volunteers recruited from, by and for the community, who help in the smooth running of health services. The role of health cadres in the healthy Indonesia program is as implementing home visits, health counseling, visiting families, collecting family data and inviting families to be able to live clean and healthy behaviors (Ministry of Health, 2016). Cadres are expected to play an active role and be able to become drivers, motivators and community educators. Community health cadres are responsible to the local community as well as leaders appointed by the health center.The total IKS of Way Halim Health Center is 0.266. From the IKS, it can be seen that the Way Halim Health Center is included in an unhealthy IKS, a healthy family is said to be if the IKS coverage (Healthy Family Index) is 0.800, a pre-healthy family is 0.500-0.800 and a family is unhealthy if the IKS 0.500 (Permenkes RI No. 39 of 2016).This research methodmemake an analytical descriptive observational researchBy using the survey method, the population in this study were all cadres at the Way Halim Public Health Center in Bandar Lampung, which amounted to 100 cadres. So that the sample in this study is the total population of 100 cadre respondents. Data analysis using quantitative descriptive analysis was carried out to answer research questions, namely analyzing the influence between variables. The results showed that the variables that had an effect on the participation of cadres at the Way Halim Public Health Center in the city of Bandar Lampung indicated that Self Efficacy had a Sig value. 0.033 where this probability value is below 0.05. Self Efficacy has an effect on Cadre Participation. Knowledge has a Sig value. of 0.016 where the probability value is less than 0.05 Knowledge affects Cadre Participation. Next, it is shown that the Motivation variable has a Sig value. of 0.029 where the probability value is below 0.05. Thus, according to the provisions of the test criteria, if the value of prob. below 0.05, then this means that partially the motivation variable has an effect on Cadre Participation. Next it is shown that the Facility variable has a value of Sig. of 0.204 where the probability value is above 0.05. Thus, according to the provisions of the test criteria, if the value of prob. 0.05, then this means that partially the Facility variable has no effect on Cadre Participation. Next, it is shown that the Group Cooperation variable has a value of Sig. of 0.000 where the probability value is below 0.05. Thus, according to the provisions of the test criteria, if the value of prob.Keywords: Participation, Cadre, Self Efficacy, Knowledge, Motivation, Facilities, and Teamwork.